2018
DOI: 10.4274/jcrpe.0134
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphatemic Familial Tumoral Calcinosis in Two Siblings with a Novel Mutation in GALNT3 gene: Experience from Southern Turkey

Abstract: Inactivating autosomal recessive mutations in both FGF23, KL and GALNT3 genes lead to a rare disorder, hyperphosphatemic familial tumoral calcinosis (HFTC). Patients with HFTC constantly present hyperphosphatemia and tumor like soft tissue calcifications. Although 78% of patients develop their first symptoms between 2-13 years of age, diagnosis is usually delayed until adulthood. Some individuals with the same genetic defect overlap a condition named Hyperphosphatemic hyperostosis syndrome (HHS). Herein we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…HHS/HFTC are rare autosomal recessive diseases (Genetic and Rare Diseases Information Center, GARD 0010879); approximately 75 cases have been genetically described worldwide [8,10,11]. They are caused by mutations in the GALNT3, FGF23, and KL genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HHS/HFTC are rare autosomal recessive diseases (Genetic and Rare Diseases Information Center, GARD 0010879); approximately 75 cases have been genetically described worldwide [8,10,11]. They are caused by mutations in the GALNT3, FGF23, and KL genes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this disorder can be either secondary to an inactivating mutation in GALNT3 preventing proper a-linked glycosylation of FGF23 or due to a mutation in the FGF23 gene. As a result, the mutations will lead to increased renal tubular phosphate reabsorption and usually elevated 1,25-dihydroxy vitamin D3, which promotes gastrointestinal absorption of calcium and phosphate [8]. As for the role of the KL gene, studies have shown that klotho is an additional cofactor that is required by FGF23 to exert its activity, as it converts canonical FGF receptors into specific receptors for FGF23, thus allowing their binding and signaling through the receptors [9].…”
Section: Introductionmentioning
confidence: 99%
“…The latter occurs due to local inflammatory reactions around calcifications or inside hyperostotic regions (1). To date, 48 cases of HFTC/HHS attributed to N-acetylgalactosaminyltransferase 3 (GALNT3) mutations (type 1 disease) have been documented, along with 21 cases of HFTC/HHS resulting from fibroblast growth factor 23 (FGF23) mutations (type 2 disease) and a single case involving a Klotho (type 3 disease) mutation (2)(3)(4)(5). Moreover, an acquired autoimmune form of HFTC/HHS has been reported, character-ized by pathogenic autoantibodies targeting FGF23.…”
Section: N Introductionmentioning
confidence: 99%